Airborne measurements of organosulfates over the continental U.S. Issue 7 (3rd April 2015) - Liao, Jin; Froyd, Karl D.; Murphy, Daniel M.; Keutsch, Frank N.; Yu, Ge; Wennberg, Paul O.; St. Clair, Jason M.; Crounse, John D.; Wisthaler, Armin; Mikoviny, Tomas; Jimenez, Jose L.; Campuzano‐Jost, Pedro; et al.
Abstract Organosulfates are important secondary organic aerosol (SOA) components and good tracers for aerosol heterogeneous reactions. However, the knowledge of their spatial distribution, formation conditions, and environmental impact is limited. In this study, we report two organosulfates, an isoprene‐derived isoprene epoxydiols (IEPOX) (2, 3‐epoxy‐2‐methyl‐1, 4‐butanediol) sulfate and a glycolic acid (GA) sulfate, measured using the NOAA Particle Analysis Laser Mass Spectrometer (PALMS) on board the NASA DC8 aircraft over the continental U.S. during the Deep Convective Clouds and Chemistry Experiment (DC3) and the Studies of Emissions and Atmospheric Composition, Clouds, and Climate Coupling by Regional Surveys (SEAC4RS). During these campaigns, IEPOX sulfate was estimated to account for 1.4% of submicron aerosol mass (or 2.2% of organic aerosol mass) on average near the ground in the southeast U.S., with lower concentrations in the western U.S. (0.2–0.4%) and at high altitudes (<0.2%). Compared to IEPOX sulfate, GA sulfate was more uniformly distributed, accounting for about 0.5% aerosol mass on average, and may be more abundant globally. A number of other organosulfates were detected; none were as abundant as these two. Ambient measurements confirmed that IEPOX sulfate is formed from isoprene oxidation and is a tracer for isoprene SOA formation. The organic precursors of GA sulfate may include glycolic acid and likely have both biogenic and anthropogenic sources. Higher aerosol acidity as measured by PALMS and relative humidity tend to promote IEPOX sulfate formation, and aerosol acidity largely drives in situ GA sulfate formation at high altitudes. This study suggests that the formation of aerosol organosulfates depends not only on the appropriate organic precursors but also on emissions of anthropogenic sulfur dioxide (SO2), which contributes to aerosol acidity.